EVALUATION OF THE SUPPLY OF MAIN TYPES OF AGRICULTURAL PRODUCTS IN UKRAINE - Burliai, A.P.; Burliai, O.L.; Zhuravel, R.O. (The actual problems of regional economy development, 2021)
Agricultural products are necessary to provide food that is safe for human health and life. That is why the assessment of the supply of agricultural products on the market in Ukraine is important and is the purpose of this study. Food supply problems are also a priority in Ukraine, which requires more detailed research. The theoretical and methodological basis of the study is the dialectical theory of knowledge and a systematic approach to the study of economic phenomena and processes, theoretical positions of domestic and foreign scientists on food security, market formation of agricultural products and crops. Structure of agricultural production by categories of farms, correlation between agricultural producers in the regions of Ukraine in Ukraine are analysed. By the supply of agricultural products we understand the amount of agricultural products that are on the market today or can be delivered there at any time. It is established that the main components of the supply of agricultural products in Ukraine are the supply of agricultural products by agricultural enterprises, households and imports. Supply of the main types of agricultural products and the structure of supply of agricultural products in Ukraine are analysed. The analysis shows that in the vast majority of products the main component of the supply of agricultural products are agricultural enterprises (more than 60%). Households predominate in those types of products that are characterized by a significant share of manual labor (fruit and vegetable products, milk). The share of imports in the supply is insignificant and ranges from 0.2 to 1%. It is confirmed that the main factor influencing the formation of the supply of agricultural products is the price. There is also a steady upward trend in prices for the main types of agricultural products in Ukraine over the past ten years: the price of grain products has increased 3.5 times, oilseeds, fruits, berries and livestock products - almost times. The export-import of domestic agricultural products for the last years is estimated.